Essays in Development and Behavioural Economics - SINGH, ANUJ PRATAP (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2019)
The core of this thesis consists of three chapters. Although on distinct topics, these chapters relate to vulnerability and financial decision making of households in Rwanda, Viet Nam and Ireland. Chapter 2 investigates the impact of micro-insurance on health seeking behaviour, out of pocket medical expenses, hardship financing, and financial outcomes of the insured. Health insurance protects households from costly health shocks, and by encouraging health seeking behaviour, can safeguard earnings and assets. The results confirm that micro-insurance serves as a social safety net by increasing health seeking behaviour and reducing out of pocket medical expenses. The chapter finds evidence for complementarity between health micro-insurance membership and formal savings activity, confirming positive spillovers between formal financial products. Further, the results indicate substitution between health micro-insurance and informal financial services, where micro-insurance crowds out both informal savings and informal borrowings. In obtaining these results, I use instrument variable estimation to correct for the issue of self-selection, an issue that undermines many previous studies. The chapter uses nationally representative cross-sectional data from Rwandan Integrated Living Conditions Survey conducted in 2005-06 and 2010-11. Chapter 3 adds to our understanding of how farmer's value agricultural insurance in Viet Nam. The chapter employs a novel approach to investigate the reasons for low demand for agricultural insurance and confirm that farmers systematically undervalue agricultural insurance. First, the chapter finds that private transfers, mainly from family members, explain under valuation of agricultural insurance. Second, membership of a farmer's union, interpreted as a form of social capital or pro-active behaviour, explains the differential between willingness to pay (WTP) and the predicted economic value of insurance. Third, the chapter helps answer the puzzle why the most risk averse are least likely to take-up agricultural insurance. The analysis finds that over-confidence holds a positive and significant relationship with WTP for agricultural insurance and interpret this as evidence that, within the context of implementation challenges and likely concerns about insurer viability, only the most confident are likely to purchase insurance. These results hold across a range of robustness checks. Chapter 4 conducts a series of online choice experiments to assess the impact of advanced consumer disclosure and misleading marketing nudges on preference for expensive cashback mortgage products. Financial products with a cashback feature typically cost consumers significantly more in the long run. Using a nationally representative online sample in Ireland, the chapter finds that consumers who are younger, less educated, suffer from present bias, and are inattentive are more likely to choose costly cash back mortgages. Further, the experiment provides strong evidence that advanced disclosure improves financial decision making of customers and that negative nudges, or advertising, encourages prospective buyers into more costly mortgages.
The Role of Insurance and Consumer Disclosure in Household Vulnerability and Financial Decision Making
APPROVED
Keywords: Household Finance; Behavioural Economics; Microinsurance; Consumer Disclosure; Willingness to Pay; Cashback Mortgage